Pengaruh Pendapatan Asli Daerah dan Dana Perimbangan Terhadap Belanja Daerah dan Budget Ratcheting sebagai Variabel Moderasi - Afli Audryna; Haryono; Juanda Astarani; Rusliyawati; Nella Yantiana (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to analyze the effect of Local Own-Source Revenue (PAD) and Balancing Funds on Regional Expenditure, with Budget Ratcheting as a moderating variable. The research was conducted on the Provincial Government of West Kalimantan for the period 2021–2023 using a quantitative approach and multiple linear regression analysis. The results showed that only Balancing Funds had a significant and positive effect on Regional Expenditure, indicating the strong dependence of regional financing on central government transfers. Meanwhile, PAD had no significant effect, suggesting limited fiscal independence in the province. Furthermore, the Budget Ratcheting variables (X1_Z and X2_Z) did not significantly moderate the relationship between PAD and Balancing Funds with Regional Expenditure. These findings highlight the need for improved local revenue management and more performance-based budgeting to reduce dependency and inefficiency in fiscal policy.